Positron annihilation in boron nitride - Amrane, N. (Condensed Matter Physics, 2006)
Electron and positron charge densities are calculated as a function of position in the unit cell for boron nitride. Wave functions are derived from pseudopotential band structure calculations and the independent particle approximation (IPM), respectively, for electrons and positrons. It is observed that the positron density is maximum in the open interstices and is excluded not only from ion cores but also to a considerable degree from valence bonds. Electron-positron momentum densities are calculated for (001,110) planes. The results are used in order to analyse the positron effects in BN.